Organizational Communication Strategies of Youth Organizations and The Impact of Changes on Youth Empowerment Efforts in Setonopande Village, Kediri City - Robingatun; Amanah, Siti (Asketik: Jurnal Agama dan Perubahan Sosial, 2024)
This research aims to describe and analyze the Karang Taruna organization's communication strategy and the impact of changes that occur from implementing this strategy. This research is a qualitative descriptive study with the research subjects being the Head of Setonopande Subdistrict, the Chair of Karang Taruna, administrators, and youth members of Karang Taruna, Setonopande Subdistrict. Using primary and secondary data with data collection techniques through observation, in-depth interviews and documentation. Data analysis used the Miles and Huberman interactive data analysis model. Based on the research results, it can be concluded that: (1). The Karang Taruna organization's communication strategy in efforts to empower youth in Setonopande Village, Kediri City has been implemented well, starting from the work program planning process, implementation to evaluation and monitoring. The communication strategy implemented has been analyzed and meets the elements of communication. (2). Youth empowerment efforts have been carried out in various forms of continuous community empowerment activities. The impact of the changes that occur can be positive or negative. However, it tends to be dominated by positive impacts, namely: being able to increase insight, knowledge, more experience, a more open mindset, more critical, more courageous, more empathetic towards other people, more agile in handling various activities, having lots of friends to discuss, lots of relationships and so on. There are only a few negative impacts, namely a high level of selfishness, so they still need guidance and direction from their seniors and this is a very common thing.